2004
DOI: 10.1139/w03-111
|View full text |Cite
|
Sign up to set email alerts
|

Cefotaximases (CTX-M-ases), an expanding family of extended-spectrum β-lactamases

Abstract: Among the extended-spectrum beta-lactamases, the cefotaximases (CTX-M-ases) constitute a rapidly growing cluster of enzymes that have disseminated geographically. The CTX-M-ases, which hydrolyze cefotaxime efficiently, are mostly encoded by transferable plasmids, and the enzymes have been found predominantly in Enterobacteriaceae, most prevalently in Escherichia coli, Salmonella typhimurium, Klebsiella pneumoniae, and Proteus mirabilis. Isolates of Vibrio cholerae, Acinetobacter baumannii, and Aeromonas hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 111 publications
5
67
0
1
Order By: Relevance
“…Other worldwide studies have documented similar findings (6,30). This increase has been attributed to the rising prevalence of the CTX-M family of ESBLs that has emerged as an important and rapidly developing problem worldwide (1,9,25).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Other worldwide studies have documented similar findings (6,30). This increase has been attributed to the rising prevalence of the CTX-M family of ESBLs that has emerged as an important and rapidly developing problem worldwide (1,9,25).…”
Section: Discussionsupporting
confidence: 56%
“…In recent years, ESBL production in Enterobacteriaceae, particularly Escherichia coli, has significantly increased in several countries, including Spain (6,21,30). This increase is primarily due to the spread of CTX-M-type ESBLs (25).…”
mentioning
confidence: 99%
“…It is conceivable that the Salmonella strains in Kuwait and UAE could have acquired the gene encoding this enzyme from E. coli and Klebsiella in the community, and then it spread among the various species and serotypes of Salmonella. This speculation is supported by the fact that the mobile genetic element ISEcpI, a single copy insertion sequence responsible for mobilization of bla genes and identified upstream of several bla CTX-M genes (Walther-Rasmussen & Høiby, 2004), was found in association with about 72 % of our isolates. The only other ESBL found in Salmonella in the Middle East is SHV-2 type, which was first reported during a nosocomial outbreak of acute gastroenteritis due to 'Salmonella wien' in a neonatal intensive care unit in Tunisia (Hammami et al, 1991).…”
Section: Discussionmentioning
confidence: 53%
“…Also, in the same study, and belonging to CTX-M group 9, we found bla CTX-M17-18 in several Salmonella serotypes (2). CTX-M group 9 enzymes are also the most common group found in other countries in Europe (28). However, it has recently become apparent that the predominant enzyme in the United Kingdom in humans seems to be CTX-M-15 (16).…”
Section: Discussionmentioning
confidence: 99%